The non-oral infection of larval Echinococcus granulosus induces immune and metabolic reprogramming in the colon of mice - Zhou, Yuying; Luo, Tiancheng; Gong, Yuying; Guo, Yuxin; Wang, Dingmin; Gao, Zixuan; Sun, Fenfen; Fu, Linlin; Liu, Hua; Pan, Wei; Yang, Xiaoying (Frontiers in Immunology, 2023)
Abstract Background: The intestinal tract serves as a critical regulator for nutrient absorption and overall health. However, its involvement in anti-parasitic infection and immunity has been largely neglected, especially when a parasite is not transmitted orally. The present study investigated the intestinal histopathology and functional reprogramming in mice with intraperitoneal infection of the larval Echinococcus granulosus (E. granulosus). Results: Compared to the control group, the E. granulosus-infected mice exhibited deteriorated secreted mucus, shorten length, decreased expression of tight junction zone zonula occludens-1 (ZO-1) and occludin in the colon. In addition, RNA sequencing was employed to characterize colonic gene expression after infection. In total, 3019 differentially expressed genes (1346 upregulated and 1673 downregulated genes) were identified in the colon of infected mice. KEGG pathway and GO enrichment analysis revealed that differentially expressed genes involved in intestinal immune responses, infectious disease-associated pathways, metabolism or focal adhesion were significantly enriched. Among these, 18 tight junction-relative genes, 44 immune response-associated genes and 23 metabolic genes were annotated. Furthermore, mebendazole treatment could reverse the colonic histopathology induced by E. granulosus infection. Conclusion: Intraperitoneal infection with E. granulosus induced the pathological changes and functional reprogramming in the colon of mice, and mebendazole administration alleviated above alternations, highlighting the significance of the colon as a protective barrier against parasitic infection. The findings provide a novel perspective on host-parasite interplay, and propose intestine as a possible target for treating parasitic diseases that are not transmitted orally.